Outras saúdes catadas: a experiência com a comunidade do Parque Ambiental Sambaiatuba - São Vicente/SP - Silva, Fábio Lopes Corrêa da [UNIFESP] (2015)
One of the major environmental problems in São Vicente, is the area where worked the "city dump" located in Sambaiatuba dike. The City hall of São Vicente closed the place, turning it into an Ecological Park but they still live in difficult conditions of exile and degradation. The objective of this study was through narratives, track, describe and provide life experiences and perhaps other health concepts, produced by the population of "pickers" Environmental Park Sambaiatuba by prospecting their habits, conflicts with the law, adopting rules, vicissitudes in labor activities, in the sociability process. Follow the desires, ways of living and salute that this population generates and sustains it formed in the course of research, an analyzer of self caring actions nowadays. This research was a possibility of bringing the approach by singularilites - questioning actions marked by prescriptions normalizing, sanitary policing, hygienism, evidence-based health, risk society, eugenics, protocols and risk factors - from their experiences and pre established health, a kind of contamination with new worlds of knowledge, pain, vitalities, ruins, joy, power and impotence. The methodology used was to retrospective research, descriptive and built from qualitative approach. the literature, or secondary sources included published literature in relation to the subject of study which, includes spare publications, books, articles, journals, literary fragments, thesis, and cartographic material. Focus group was used as a data production instrument, data field notes, semi-structured interviews and affective maps that converged to all creation narratives in a shrt story format. Those data were established operating with the cartographic device proposed by Gilles Deleuze and Felix Guattari and the problems were built during the research experience and not from ready structural models or pre-drawn paths. Integrated research through the narrative, the old "pickers", now members of Coopercial of the stories here related. In these writings were attending problems that envolves issues and health concepts. Many questions emerged in the research as the multiple ecologies (not just environmental ecology), problems involving risk-animality and sanitary police, the displacement of health care as ambassador of a sad and asepctic health, the issue of "unimportant lifes" that anyway care. The material produced allowed the construction of a film, called Coragyps atratus, made from compilations of other productions that echoed with what is investigating, along with material shot in site. The "model" health first introduced to this community did not produce effects in resonance with them, your organization differed much from those recommended by the norms. The needing of going trough and being trough by the ways of life the community, were essesntial to discuss this research was only possible when an availability of research allowed me to walk around with a bag and "pick healths" and singularities with the eyes of who wants to see in the dark of contemporary and be closers to theis worlds.